Households in Transit: COVID-19 and the Changing Measurement of Welfare - Laura Caron; Erwin R. Tiongson (Institute of Labor Economics (IZA), 2022)
The COVID-19 pandemic placed new constraints and prices on commuting to work around the world. However, traditional methods of measuring household welfare (and, accordingly, poverty and inequality) based on expenditures have not considered these changes. First, we present theory showing significant mismeasurement of welfare for households who can shift into remote work during the pandemic. We then propose methods to impute transportation cost equivalents for household expenditure aggregates. We use Georgia as a case study to compare these methods and assess impacts on poverty and inequality. The proportion of remote work is low, only about 9%, meaning that the impact on overall inequality is negligible. However, considering transportation costs can result in up to a 40% reduction in the measured poverty rate among remote-working households.
Keywords: I32; D30; R20; J32; 330; poverty measurement; inequality measurement; consumption aggregate; expenditures; imputation; living costs; COVID-19; welfare